The Indigenous history and colonial politics of Torres Strait: contesting culture and resources from 1867 to 1990 - Pitt, George Henry (Curtin University, 2005)
The aim of my study is to comprehend why there is a significant gap in the economic development of Torres Strait. It questions why it is that Torres Strait Islanders as a whole remain largely economically unproductive in their present situation in contrast to the political beliefs of Islanders and their struggles for self-determination. It questions why Island leaders continue to accept policies of external control even though the guidelines for self development maintain the situation, rather than transforming it. Thus this thesis examines contemporary and traditional history of the Torres Strait in order to analyse and evaluate the development of the political structures of the Islands and how colonialism has influenced the politics of Torres Strait Islanders. I shift through the recorded layers of myths and legends for my interpretation and analyse the ethnographic accounts about Torres Strait from past archival reports, academic literature and the oral accounts from interviews. From the local media, I have examined the recent views of both the contented and discontented Islanders and other people reported in the local Torres News. From these records, I bring into perspective the historical processes of a capitalist economic system which has so deeply penetrated Islander culture.Commencing in the 1860s, at the onset of the Torres Strait beche-de-mer and pearl shell industry, the system has so failed Torres Strait Islanders' social development that it moved Islander leaders in the 1980s to push for cessation from Australia and, in the mid 1900s to seek "autonomy and self government" to remain within the Australian political system. In this thesis, I use this evidence to bring into perspective the concept of development with awareness to the colonial history of Torres Strait in comparison with oral history interpreted as the culture of my people. The theme my thesis implicates the contestation between Torres Strait Islanders and governments who impose administrative policies through the Islander system of political representation (regarding Islander culture and resources).